2011
DOI: 10.1164/rccm.201011-1887oc
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Ventilated Patients According to Time to Liberation from Mechanical Ventilation

Abstract: Patients were classified according to a new weaning classification: 1,502 patients (55%) as simple weaning,1,058 patients (39%) as difficult weaning, and 154 (6%) as prolonged weaning.Variables associated with prolonged weaning(.7d)were: severity at admission (odds ratio [OR] per unit of Simplified Acute Physiology Score II, 1.01; 95% confidence interval [CI], 1.001–1.02), duration of mechanical ventilation before first attempt of weaning (OR per day, 1.10; 95% CI, 1.06–1.13), chronic pulmonary disease other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
3
19

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(211 citation statements)
references
References 20 publications
7
182
3
19
Order By: Relevance
“…Among the reasons for ICU admission, 66% of the patients had respiratory causes, and most of them were diagnosed with pneumonia in this study. A previous study showed that the incidence of chronic pulmonary diseases, with exception to COPD, postoperative acute respiratory failure, and pneumonia, was associated with difficult and prolonged weaning in patients with MV (27). COPD was not associated with weaning failure following a multivariate analysis in the present study.…”
Section: Discussionsupporting
confidence: 43%
“…Among the reasons for ICU admission, 66% of the patients had respiratory causes, and most of them were diagnosed with pneumonia in this study. A previous study showed that the incidence of chronic pulmonary diseases, with exception to COPD, postoperative acute respiratory failure, and pneumonia, was associated with difficult and prolonged weaning in patients with MV (27). COPD was not associated with weaning failure following a multivariate analysis in the present study.…”
Section: Discussionsupporting
confidence: 43%
“…In this analysis, 2,714 patients were successfully discontinued over the 28 day study period. 23 Fifty-five percent were simple discontinuation, 39% were difficult discontinuation, and 6% were prolonged discontinuation. Not surprisingly, patients needing prolonged discontinuation processes were sicker and had longer stay and higher mortality than the simple discontinuation patients.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Severity of illness has been associated with prolonged weaning, longer duration of mechanical ventilation, and need for a tracheostomy. 17 Timing of tracheostomy after intubation was significantly longer in patients who had an infection before the tracheostomy. The infection most likely impaired weaning from mechanical ventilation, necessitating prolonged ventilatory support and causing difficulty in weaning.…”
Section: Discussionmentioning
confidence: 97%